Antitumor effects of polysaccharides from Tetrastigma hemsleyanum Diels et Gilg via regulation of intestinal flora and enhancing immunomodulatory effects in vivo - Zhou, Fangmei; Lu, Yan; Sun, Tong; Sun, Ling; Wang, Bixu; Lu, Jingjing; Li, Zhimin; Zhu, Bingqi; Huang, Shigao; Ding, Zhishan (Frontiers in Immunology, 2022)
Tetrastigma hemsleyanum Diels et Gilg is a traditional Chinese herbal medicine with high medicinal value, and antitumor, antioxidant and anti-inflammatory biological activities. However, while several studies have focused on flavonoids in Tetrastigma hemsleyanum tubers, there are few studies on the enhanced immune effect of Tetrastigma hemsleyanum polysaccharides (THP). In this study, we evaluated the antitumor effect of THP in a lung tumor model and explored the mechanism of antitumor activity through intestinal flora. In addition, a cyclophosphamide (CTX)-induced immunosuppression model was used to declare the immunomodulatory effect of THP in the immunosuppressive state induced by antitumor drugs. The results showed that THP increased the content of ileum secreted immunoglobulin A (SIgA) and cecum short-chain fatty acids (SCFAs) and improved microbial community diversity, regulating the relative abundance of dominant microbiota flora from the phylum level to the genus level, and recovering the intestinal microflora disorder caused by tumors. Additionally, THP can increase the organ indices and improve immune organ atrophy. THP can upregulate routine blood counts and stimulate the production of the serum cytokines. THP also promoted the macrophage phagocytic index, NK-cell activation, and complement and immunoglobulin (IgG, IgA, IgM) levels. The detection of Splenic lymphocyte proliferation and T lymphocyte subsets also sideways reflects that THP can restore CTX-induced immune inhibition in mice. In conclusion, this study suggests that THP can effectively achieve the enhanced antitumor effects, regulate gut microbiota and improve the immunosuppression induced by antitumor drugs. Therefore, THP can enhance the immune capacity and provide novel immunomodulatory and antineoplastic adjuvant agents.